Ruthenium‐Catalyzed Vinylene Carbonate Annulation by C−H/N−H Functionalizations: Step‐Economical Access to Indoles. Issue 4 (5th January 2022) - Yu, Yao; Wang, Yang; Li, Bo; Tan, Yuqiang; Zhao, Huan; Li, Zheyu; Zhang, Chunran; Ma, Wenbo
Abstract: A convenient and effective method of ruthenium‐catalyzed C−H/N−H annulations using vinylene carbonate as oxidizing acetylene surrogate has been disclosed. This method is scalable and compatible with a wide range of functional groups, providing a step‐economical access to indole synthesis Preliminary mechanistic studies provided support for a reversible, acetate‐assisted C−H ruthenation, along with a subsequent olefin insertion. Abstract :